2021
DOI: 10.1038/s41467-021-24629-0
|View full text |Cite
|
Sign up to set email alerts
|

Decision-related feedback in visual cortex lacks spatial selectivity

Abstract: Feedback in the brain is thought to convey contextual information that underlies our flexibility to perform different tasks. Empirical and computational work on the visual system suggests this is achieved by targeting task-relevant neuronal subpopulations. We combine two tasks, each resulting in selective modulation by feedback, to test whether the feedback reflected the combination of both selectivities. We used visual feature-discrimination specified at one of two possible locations and uncoupled the decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 67 publications
0
24
0
Order By: Relevance
“…Thus, the full model describes the population response as Thus, the parameters of the model are the stimulus tuning parameters A , the shared gain, g , the gain loadings, w g , and the offsets, b . To capture any unit-specific slow drifts in firing rate, we further parameterized b as a linear combination of 5 b0-splines evenly spaced across the experiment 49 . Thus, the baseline firing rate for each neuron, i , was a linear combination of 5 “tent” basis functions spaced evenly across the experiment, b i = ∑ j b j φ j ( t ).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the full model describes the population response as Thus, the parameters of the model are the stimulus tuning parameters A , the shared gain, g , the gain loadings, w g , and the offsets, b . To capture any unit-specific slow drifts in firing rate, we further parameterized b as a linear combination of 5 b0-splines evenly spaced across the experiment 49 . Thus, the baseline firing rate for each neuron, i , was a linear combination of 5 “tent” basis functions spaced evenly across the experiment, b i = ∑ j b j φ j ( t ).…”
Section: Methodsmentioning
confidence: 99%
“…Disparity Discrimination: Animal M2 performed a disparity discrimination task (right panel of Fig. 1B) previously described in detail 52 . Briefly, once the animal fixated on a FP (0.1° diameter), two circular dynamic random-dot stereograms (RDSs, for details see Visual Stimuli), consisting of a disparity-varying center surrounded by an annulus fixed at zero disparity, were presented, one in each visual hemifield.…”
Section: Behavioral Tasksmentioning
confidence: 99%
“…It has been shown that field potentials (e.g., eCoG) are associated with calcium plateau potentials in apical dendrites of layer-5 pyramidal neurons ( Suzuki and Larkum, 2017 ), and these same potentials are capable of inducing plastic changes at relevant time scales (e.g., behavioral time scale plasticity, Magee and Grienberger 2020 ). Such plateau potentials and their biochemical sequelae might allow long range projections—especially feedback—to identify their targets, or for the targets of the projections to establish a state of receptivity to a signal that is broadcast widely ( Quinn et al, 2021 ). This would be a convenient way for feedback projections to pick out the causes of the activity that is feeding back.…”
Section: Discussionmentioning
confidence: 99%